2009
DOI: 10.1097/pas.0b013e3181b314ce
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bone Diffuse Large B-cell Lymphoma

Abstract: Primary bone diffuse large B-cell lymphomas (PB-DLBCL) are uncommon extranodal lymphomas. Herein, we report the clinical, pathologic, immunohistochemical, and molecular features of 21 cases of PB-DLBCL. The mean age of the patients was 54 years (range: 13 to 85 y). The male and female ratio was 1.6:1. The tumors consisted of diffuse sheets of large atypical cells or a polymorphous mixture of small-to-large cells with large multilobated nuclei, fine chromatin, and inconspicuous to prominent nucleoli. Twelve (57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 11 publications
4
9
0
Order By: Relevance
“…A previous study aimed at nodal DLBCL, suggested that the prognosis of the GCB subtype is better than that of the non-GCB subtype in using standard chemotherapy 37 . In our study, 23 cases of 34 PB-DLBCL patients could be further divided into GCB type (11 cases) and non-GCB type (12 cases), but the 5-year OS and PFS between the 2 groups did not reach statistical significance, which is in accordance with reports from Bhagavathi et al 38 and Heyning et al 31 , but the sample sizes were small and the influence of molecular subtypes on prognosis remains to be elucidated.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study aimed at nodal DLBCL, suggested that the prognosis of the GCB subtype is better than that of the non-GCB subtype in using standard chemotherapy 37 . In our study, 23 cases of 34 PB-DLBCL patients could be further divided into GCB type (11 cases) and non-GCB type (12 cases), but the 5-year OS and PFS between the 2 groups did not reach statistical significance, which is in accordance with reports from Bhagavathi et al 38 and Heyning et al 31 , but the sample sizes were small and the influence of molecular subtypes on prognosis remains to be elucidated.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the subclassification of PBL, several studies with small sample sizes have described the IHC characteristics of PB-DLBCL [ 18 21 ]. In these previous reports, approximately half of the PB-DLBCL cases demonstrated a germinal center B-cell (GCB) phenotype by IHC with high Bcl-2 and/or Bcl-6 expression and relatively low MUM-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite so, 26 of 43 patients were able to be classified with PB-DLBCL in our series according to CD10-positivity, which meant that at least 60.5% of these patients were of GCB phenotype. Prior studies have yielded conflicting results about the predictive value of these IHC markers, particularly of CD10 and GCB stubtype [ 5 , 18 21 ]. Although insufficient for subclassification of GCB or non-GCB subtype of PB-DLBCL, our limited data showed no association between various markers (CD10, Bcl-6, Bcl-2, MUM-1) and survival in PB-DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The histological and immunohistochemical appearance of PBL has been reported in a number of studies [ 2 , 3 , 4 , 7 , 8 , 9 , 14 , 15 , 16 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ,…”
Section: Histological Findingsmentioning
confidence: 99%